Commitment or Even Compliance? An Australian University's Approach to Equal Employment Opportunity - North-Samardzic, Andrea; Gregson, Sarah (Relations industrielles / Industrial Relations, 2011)
This paper presents empirical evidence to illustrate how one Australian university complies with the nation's federal Equal Employment Opportunity (EEO) regulatory framework. The aim of this paper is to provide insight into the extent to which organizational practices deviate from articulated policy and how this gap impacts on the perceived career trajectories of female academics. While the disadvantaged status of female academics has been recognized worldwide, a deeper examination of how employees experience the policies and practices designed to support their advancement is required, especially in light of the increasing corporate-like activities of Australian universities which have deprioritized EEO. A case study of an Australian university is used to explore these phenomena. Documentary evidence of its EEO policies was compared with interviewee narratives of employees, including both female academics and members of general staff involved in policy development. This allowed female employees to be heard, in particular where they sensed contradictions between espoused company policy and their real experiences. Hearing what they have to say is an important contribution, given that Australia's EEO regulatory framework allows organizations to waive reporting on their gender equity “chievements.”This case study highlights employee concerns about the efficacy of the University's policies and practices designed to support women's career trajectories and demonstrates that, particularly in light of the increasing corporatization of the University, some women questioned whether drawing support from such policies would harm their careers. The most signifi cant concern focused on the criteria for promotion, which interviewees perceived to be based on a masculine model of merit, in contrast to the ostensible gender-neutrality of the promotions policies. A related concern was how carer responsibilities impacted on opportunities for advancement, particularly the ability to engage in research work that was prized more highly than teaching activities by promotions committees. These examples illustrate that, while the University may be upholding the law at face-value, the actual experiences of women in the organization suggest that EEO compliance is merely skin-deep.